Badania Pewnych Reologicznych Własności Elastooptycznych Kilku Żywic Poliestrowych (III) - Pindera, J.T. (Engineering Transactions, 1959)
This is the last of a set of papers on the investigations of the rheologic properties of photoelastic materials, containing conclusions from the author’s investigations carried out hitherto. The author gives a characteristic of the materials tested from the point view of the accuracy of measurement and formulates general criteria of suitability of a material for the purpose of making linearly elastic models, taking creep phenomena into consideration. Several new investigation methods are proposed such as the dynamic method for eliminating the photoelastic creep, the dynamic method for reducing the time of creep and relaxation tests and the dynamic method for testing stress fields in the neighbourhood of notches in thick plates. Requirements for experimental investigations of the most characteristic properties of photoelastic materials are established. The paper contains a description of a universal photoelastic polariscope satisfying the requirements following from the analysis of the test results. The following conclusions are drawn from the results obtained. At the present state of development of the photoelastic methods it is necessary.to intensify the investigations of the rheologic properties of photoelastic materials such as creep, relaxation, creep and relaxation recovery, vibro-creep and vibro-relaxation, and to widen their scope. The interpretation of the photoelastic relations should be based on the results of investigations of the structure of the material and its physical and chemical properties. Investigations of the properties of photoelastic materials by means of prismatic test pieces subjected to pure bending does not enable us, in view of the complexity of the rheologic processes, to obtain correct results. Therefore investigations by means of test-pieces under possibly one-axial and homogeneous strees should be treated as a basic investigation of the rheologic properties in photoelasticity. It is proposed to perform photoelastic creep tests using test-pieces in the form of slender wedges passing into prismatic parts. The test results did not confirm the suppositions that the change of dispersion of the birefringence may constitute a general measure of plastic strain of photoelastic materials. The characteristic forms of curves of photoelastic creep and recovery observed may be explained by assuming that photoelastic creep, recovery and durable photoelastic effect are above all a function of orientation of various anisotropic groups the rotation of which depends on the degree of cross-linking of the material. This interpretation enables us to draw a number of practical conclusions, among others conclusions concerning the preparation of photoelastic materials of desired rheologic properties and concerning the freezing method. Investigations have shown that the rheologic type of the materials tested differs from that of the combined linear Maxwell-Kelvin model. Further investigations are announced.